The Arterial Anatomy of the Deltoid Ligament: A Cadaveric Study. (July 2017) - Haynes, Jacob A.; Gosselin, Michelle; Cusworth, Brian; McCormick, Jeremy; Johnson, Jeffrey; Klein, Sandra
Background: There is an increasing interest in the operative treatment of deltoid ligament disruption in the setting of chronic ankle instability. Understanding the vascular anatomy of the deltoid complex is beneficial when considering operative procedures on the medial ankle and may provide insight into factors that lead to chronic deltoid insufficiency and ankle instability. Methods: Thirty-two pairs of cadaveric specimens (64 total legs) were amputated below the knee, and the tibialis anterior, tibialis posterior, and peroneal arteries were injected with India ink and Ward's blue latex. Specimens then underwent chemical debridement to identify the vascular supply to the deltoid ligament. A subset of specimens also underwent intraosseous debridement using the modified Spalteholz technique. Results: The vascular supply to the deltoid ligament was clearly visualized in 60 (93.8%) specimens. Fifty-eight specimens (96.7%) had arterial supply with an origin from the medial tarsal artery, 57 specimens (95%) had supply from the tibialis posterior artery, and 23 (38.3%) specimens had supply from the tibialis anterior artery. All specimens had at least 1 location of intraosseous vascular supply, either at the medial malleolus or medial talus. Conclusion: There were 3 separate extraosseous sources and 2 intraosseous sources of vascular supply to the deltoid ligament. Clinical Relevance: Knowledge of the vascular supply may aid in identifying factors that predispose a subset of patients with medial ankle sprains to failure of conservative treatment, as well as provide useful anatomic information when considering operative treatment for chronic ankle instability.